Clinical features of gastroenteropancreatic tumours - Gut, Paweł; Czarnywojtek, Agata; Bączyk, Maciej; Ziemnicka, Katarzyna; Fischbach, Jakub; Wrotkowska, Elżbieta; Ruchała, Marek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Gastroenteropancreatic (GEP) endocrine tumours (carcinoids and pancreatic islet cell tumours) are composed of multipotent neuroendocrine cells that exhibit a unique ability to produce, store, and secrete biologically active substances and cause distinct clinical syndromes. The classification of GEP tumours as functioning or non-functioning is based on the presence of symptoms that accompany these syndromes secondary to the secretion of hormones, neuropeptides and/or neurotransmitters (functioning tumours). Non-functioning tumours are considered to be neoplasms of neuroendocrine differentiation that are not associated with obvious symptoms attributed to the hypersecretion of metabolically active substances. However, a number of these tumours are either capable of producing low levels of such substances, which can be detected by immunohistochemistry but are insufficient to cause symptoms related to a clinical syndrome, or alternatively, they may secrete substances that are either metabolically inactive or inappropriately processed. In some cases, GEP tumours are not associated with the production of any hormone or neurotransmitter. Both functioning and non-functioning tumours can also produce symptoms due to mass effects compressing vital surrounding structures. Gastroenteropancreatic tumours are usually classified further according to the anatomic site of origin: foregut (including respiratory tract, thymus, stomach, duodenum, and pancreas), midgut (including small intestine, appendix, and right colon), and hindgut (including transverse colon, sigmoid, and rectum). Within these subgroups the biological and clinical characteristics of the tumours vary considerably, but this classification is still in use because a significant number of previous studies, mainly observational, have used it extensively.